Dimensions of Forceful Displacements in Nigeria: Is Administration of Humanitarian Assistance Skewed towards those Displaced by Violent Conflicts? - Adekola, Paul O.; Akintuyi, Olatubosun B; Adeyemi, Gideon (European Journal of Applied Sciences, 2024)
Forceful displacement in Nigeria is mainly caused by violent conflict, urban renewal, climate change, and oil exploration, among others. However, humanitarian assistance in its various dimensions from the government, non-governmental organizations (NGOs) and other donor agencies have been skewed mostly towards those displaced by violent conflict. This position paper examines the implications of this imbalance in access to humanitarian assistance particularly among those displaced through urban renewal and oil exploration. Rather than testing hypotheses, this article relies on a robust review of the literature to answer research questions related to the differences and implications of humanitarian assistance individuals displaced by gentrification and oil exploration receive as compared to what individuals displaced by violence receive. Findings from reviewed empirical articles show most assistance goes to those displaced by violent conflict and that poverty, destruction of the means of livelihood, depression, child marriage, unemployment and poor inter-spousal communication are some of the direct and/or indirect implications of forced displacement through urban renewal and oil exploration in Nigeria. We maintain a position that this partial and lopsided response is counterproductive and recommend that the government extend similar gestures to those displaced through urban renewal and oil exploration to alleviate deep poverty and other socio-economic effects found in the reviewed articles.